Determination of Folic Acid with a Novel Biomass Sourced Carbon Quantum Dots-Mesoporous Silica Fluorescent Probe - Wen, He; Lim, Soh Fong; Rubiyah, Baini; Jie, Lu; Yingdi, Zheng (Royal Society of Chemistry, 2024)
Folic acid (FA) is a crucial vitamin for the human health, and imbalanced levels of folate can result in various illnesses. A new fluorescent probe called CQDs-MSN, made from biomass carbon quantum dots and mesoporous silica, was developed through hydrothermal and template techniques to detect FA concentrations. By studying the fluorescence response and linear correlation ofthe CQDs-MSN with FA, the optimal conditions were determined by adjusting the reaction time and pH level.The findings indicated that the best fluorescence quenching effect occurred when the pH was 7.4, and the reaction time was 4 min. At λex=355 nm and λem=427 nm, the fluorescence emission spectra of CQDs-MSN were notably reduced due to the combined effects of static quenching and internal filtering effect when FA was present. Under optimal conditions, the detection concentration for FA ranged from 0 to 100.0 µM, with a limit of 0.18 µM. Furthermore, CQDs-MSN were effectively utilized to measure FA in real samples, including urine and rabbit serum, achieving spiked recoveries between 98.7% and 102.3%. These demonstrated that the CQDs-MSN is a suitable tool for analysing FA in biosensing applications.